The genesis of polymorbidity in elder female & the role of neuronspecific enolase - G N Sovenko; K I Prashchayeu; M A Chizhova; M I Churnosov; A N Ilnitski (RUDN Journal of Medicine, 2010)
The problem of correlation between polymorbidity and neuronspecific enolase is presented in this article.